Sketching the Moon An Astronomical Artist's Guide - Handy, Richard; Kelleghan, Deirdre; McCague, Thomas; Rix, Erika; Russell, Sally; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
Soon after you begin studying the sky through your small telescope or binoculars, you will probably be encouraged by others to make sketches of what you see. Sketching is a time-honored tradition in amateur astronomy and dates back to the earliest times, when telescopes were invented. Even though we have lots of new imaging technologies nowadays, including astrophotography, most observers still use sketching to keep a record of what they see, make them better observers, and in hopes of perhaps contributing something to the body of scientific knowledge about the Moon. Some even sketch because it satisfies their artistic side. The Moon presents some unique challenges to the astronomer-artist, the Moon being so fond of tricks of the light. Sketching the Moon: An Astronomical Artist$1 (Bs Guide, by five of the best lunar observer-artists working today, will guide you along your way and help you to achieve really high-quality sketches. All the major types of lunar features are covered, with a variety of sketching techniques applied to each. These techniques are explained and illustrated in ways that take the mystery out of artwork, rendering it (so to speak) more accessible to those observers interested in going farther than merely illustrating their notes. So use this comprehensive and easy to follow guide to make astronomy more than science for you$1 (Bmake it also an art!s
Foreword -- Preface -- Key to Map of Featured Targets -- Basic Sketching: A Place to Begin -- Chapter 1: Sketching Craters -- Chapter 2: Sketching Maria (Seas) -- Chapter 3: Sketching Mons (Mountains) -- Chapter 4: Sketching Rilles (Lava Channels) -- Chapter 5: Sketching Dorsa (Wrinkle Ridges) -- Chapter 6: Sketching Crater and Sunlight Rays -- Chapter 7: Sketching Rupes (Scarps) -- Chapter 8: Sketching the Phases -- Chapter 9: Sketching Domes -- Chapter 10: Sketching Lunar Eclipses -- Chapter 11: Additional Tutorials and Sketching Gallery -- Chapter 12: General Hints and Tips -- A Final Note from the Authors -- Appendix A: Observing Forms -- Appendix B: Glossary -- Appendix C: Resources -- Index.
Keywords: Physics; Astronomy; Humanities; Physics; Astronomy, Observations and Techniques; Popular Science in Astronomy; Arts Education; Fine Arts